Specific Vaginal Bacteria Are Associated With an Increased Risk of Trichomonas vaginalis Acquisition in Women - Jarrett, Olamide D (J Infect Dis, 2019)
BACKGROUND: While bacterial vaginosis has been associated with an increased risk of Trichomonas vaginalis (TV) acquisition, it is unknown whether other characteristics of the vaginal microbiota, including the presence of key bacterial species, influence a woman’s risk of TV acquisition. METHODS: The vaginal microbiota before 25 unique episodes of TV infection involving 18 women was compared to that of 50 controls who remained uninfected. TV was detected by transcription-mediated amplification. Vaginal microbiota were quantified using broad-range polymerase chain reaction analysis and taxon-specific quantitative PCR of the 16S ribosomal RNA gene. RESULTS: TV acquisition was significantly associated with the presence of Prevotella amnii (risk ratio [RR], 2.21; 95% confidence interval [CI], 1.12–4.38; P = .02) and Sneathia sanguinegens (RR, 2.58; 95% CI, 1.00–6.62; P = .049). When adjusted for menstrual phase, the association between P. amnii and TV acquisition remained similar (adjusted RR, 2.11; 95% CI, 1.03–4.33; P = .04), but the association between S. sanguinegens and TV acquisition was attenuated (adjusted RR, 2.31; 95% CI, .86–6.23; P = .10). CONCLUSIONS: Key vaginal bacterial species may contribute to the susceptibility to TV acquisition. Understanding how these bacterial species increase a woman’s risk of TV acquisition could help to guide the development of novel strategies to reduce women’s risk of TV infection.